Vortioxetine for Cognitive Enhancement in Major Depression: From Animal Models to Clinical Research - Bennabi, Djamila; Haffen, Emmanuel; Van Waes, Vincent (Frontiers in Psychiatry, 2019)
Objectives: Vortioxetine, has already shown its efficacy in the acute and long-term treatment of MDD, and its interest in the prevention of relapse. The aim of this study was to review the current status of knowledge regarding cognitive effects of vortioxetine. Methods: We conducted a review of key data obtained from preclinical behavioral models and clinical trials in MDD focusing on vortioxetine-induced cognitive changes. Results: In animal, acute and chronic administration of vortioxetine improved performance on objective measures that cover a broad range of cognitive domains. In human, vortioxetine appears as a useful treatment option in patients with MDD, especially in the presence of cognitive dysfunction. Conclusion: Vortioxetine constitutes a promising treatment for treatment of cognitive impairment in MDD, but its place in the therapeutic armamentarium still need to be determined.